ANALISIS VARIASI PANJANG SERAT TERHADAP KUAT TARIK DAN LENTUR PADA KOMPOSIT YANG DIPERKUAT SERAT Agave angustifolia Haw - Bakri, Bakri; Iqbal, Mohammad; Rifki, Mohammad (Jurnal MEKANIKAL, 2012)
Natural fibre composites have been developed for some applications. One of potential natural fibre for composite is angustifolia Haw Agave fibre. In this research, the tensile strength and flexural strength of agave fibre composite with variations of fibre length were determined. Fibre agave (treated and untreated) with 1 cm, 3 cm and 5 cm length was used as reinforced composite. The results showed that the maximum tensile strength of agave fibre composite with untreated fibre occurs in 5 cm length, meanwhile with treated fibres the tensile strength tends to similar for each fibre length; and agave fibre with 5 cm length as reinforced composite has higher flexural strength than other fibre lengths for treated and untreated fibres.